Organisational Coaching Outcomes: A comparison of a practitioner survey and key findings from the literature - Sheila Boysen; Michael Cherry; Wende Amerie; Mike Takagawa (International Journal of Evidence Based Coaching and Mentoring, 2018)
This paper compares the measurements of organisational outcomes from executive and leadership coaching based on existing studies and research that has been conducted throughout the literature. An overview of executive and leadership coaching is provided and a case study measuring executive and leadership coaching effectiveness is reported. The survey methodology used in this case study was not originally intended for an academic research design, rather it was a customer satisfaction survey. However, the results can provide insights into the value, ROI and impact of executive and leadership coaching.